2007
DOI: 10.1080/10731190601188422
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV Nucleocapsid Protein Induced Apoptosis of COS-1 Mediated by the Mitochondrial Pathway

Abstract: To investigate the apoptosis effect of SARS coronavirus nucleocapsid protein on cultured cell lines and to explore the possible pathway of apoptosis. pCDNA3.1(-)/his-myc vector containing the SARS coronavirus nucleocapsid gene (N), matric gene (M), spike gene (S) were transfected into COS-1, Huh-7 and HepG2 cells. Apoptosis induced by SARS coronavirus N protein under starvation of serum of COS-1 cells was monitored by Annexin V and electron microscopy assays. Intracellular reactive oxygen species (ROS) and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
(32 reference statements)
1
41
0
1
Order By: Relevance
“…Previous studies have shown that overexpression of Bnip3 results in its integration into the outer mitochon-drial membrane with specific orientationits N-terminus in the cytoplasm and C-terminus in the membrane (41). After integration into the mitochondrial membrane, Bnip3 can interact with components of MPT pores to induce their rapid opening and dissipation of DΨm, followed by apoptotic cell death (42). We have also proven that CoCl 2 promoted activation of HIF-1a, upregulated expression of HIF-1a and Bnip3, and ultimately resulted in apoptosis of the cells; this could be attenuated by use of NAC, an inhibitor of HIF-1 a.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that overexpression of Bnip3 results in its integration into the outer mitochon-drial membrane with specific orientationits N-terminus in the cytoplasm and C-terminus in the membrane (41). After integration into the mitochondrial membrane, Bnip3 can interact with components of MPT pores to induce their rapid opening and dissipation of DΨm, followed by apoptotic cell death (42). We have also proven that CoCl 2 promoted activation of HIF-1a, upregulated expression of HIF-1a and Bnip3, and ultimately resulted in apoptosis of the cells; this could be attenuated by use of NAC, an inhibitor of HIF-1 a.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was not observed in another cell line of epithelial lineage (huh7). Recently, Zhang et al (2007) have reported that serum starvation apoptosis of N expressing COS-1 cells involves activation of mitochondrial pathway. It remains to be studied whether this phenomenon is actually recapitulated in vivo.…”
Section: Induction Of Apoptosis In Serum Starved Monkey Kidney Cellsmentioning
confidence: 99%
“…Among the proteins, N, as the RNA-binding protein, play an important role in both virus RNA synthesis and modulating host cell processes, and phosphorylation may regulate these processes by exposing various functional motifs [4,5]. Several other functions have been postulated for the coronavirus N protein throughout the virus life cycle, including encapsidation, packaging, correct folding of the RNA molecule, the deregulation of the host cell cycle [6,7,8], inhibition of interferon production [9,10], up-regulation of COX2 production [11,12], up-regulation of AP1 activity [13], induction of apoptosis [14,15,16], association with host cell proteins [17], and RNA chaperone activity [18]. Therefore, it is clear that N is a multifunctional protein involved in biological processes related to the survival of PEDV.…”
Section: Introductionmentioning
confidence: 99%